Windows sharepoint services 3.0 inside out - O’Connor, Errin (Microsoft Press, 2008)
Learn everything you need to know for working with Microsoft Windows SharePoint Services Version 3.0--from the inside out! This book packs hundreds of time-saving solutions, troubleshooting tips, and workarounds for using Windows SharePoint Services--all in concise, fast-answer format. This information-packed complete reference shows you how to get the most out of Windows SharePoint Services. You will learn how to simplify information sharing, make team collaboration more efficient, and improve your personal productivity. You'll discover how to design workflows and projects for SharePoint sites, manage design teams and source control, and use cascading style sheets to control site appearance. You'll get to explore new features for using Windows SharePoint Services with blogs, RSS, and wikis. You'll even learn how to use Windows SharePoint Services with other products, including Microsoft Office Excel® Services, Microsoft Office Project Server 2007, and Microsoft Visual Studio® 2005 Team System. Plus, the companion CD includes the complete eBook, Insider Extras, and the electronic version of both the Tablet PC Quick Reference and the Microsoft Computer Dictionary. With INSIDE OUT, you get all muscle and no fluff!